Defectos congénitos en un hospital de tercer nivel en Cali, Colombia (2015)
To determine the overall and individual prevalence of birth defects diagnosed at birth in a referral hospital in Cali, Colombia, in the period 2011-2012 and compare the results with previously reported for the same institution. Methods: Epidemiological surveillance of birth defects was performed at the Hospital Universitario del Valle between July 2011 and June 2012, following ECLAMC methodology. Tables were performed to illustrate the frequency distribution of birth defects. Results: During the 12 months of study there were 5,669 births, of which 109 had at least one birth defect, for a prevalence of 1.92[%]. For specific birth defects, the highest prevalence were recorded for polydactyly (24.69 × 10,000), auricular appendage (15.87 × 10,000), hydrocephalus (15.87× 10,000), hydrocephalus (15.87 × 10,000). By grouping, the highest prevalence was for the following groups: limb defects (79.37× 10,000), central nervous system defects (49.39 × 10,000), vascular disruption defects (40.57 × 10,000). Conclusions: In the surveillance period in the institution it was found a prevalence of birth defects similar to that previously reported in the same institution. By grouping, the highest prevalence were for limb defects, defects of the central nervous system and vascular disruption defects. Birth defects associated with environmental factors, principally neural tube defects and defects by vascular disruption had higher prevalence compared with those reported previously.